(untitled) (JURNAL IBU DAN ANAK, 2022)
Toddler sleep conditions are a very big influence on the growth of toddlers, so that the quality of toddler sleep must be carried out optimally. In supporting the sleep quality of toddlers, it is necessary to implement murottal Al-Quran therapy as a religious therapy. Based on the initial survey, there are toddlers who experience sleep disorders on the grounds that there are children who are fussy, have difficulty sleeping and often wake up in their sleep. This type of research is quantitative with a pre-experimental model with a population of 30 toddlers and a sample of 15 toddlers using purposive sampling technique. This research was conducted in January – April 2022 by conducting observations and questionnaire sheets. The analysis in this study used a paired t-test. The results obtained are that there is an effect of murottal Al-Qur’an on the sleep quality of toddlers aged 1-2 years in Rimbo Panjang Village, Mining Health Center Work Area with a correlation value of 0.002 with a value of 0.05. It is recommended to parents of toddlers to improve the implementation of murottal Al-quran therapy to improve the quality of sleep for toddlers.